2022
DOI: 10.1186/s12885-022-10190-6
|View full text |Cite
|
Sign up to set email alerts
|

Oncologist approaches to communicating uncertain disease status in pediatric cancer: a qualitative study

Abstract: Background Most patients with cancer and their caregivers desire honest, clear prognostic communication, yet oncologists often disclose prognosis inconsistently. Prognostic communication becomes even more challenging when disease progression is unclear or equivocal. Presently, oncologist approaches for discussing uncertain disease findings are poorly understood. Methods In this prospective, longitudinal study, we audio-recorded serial disease reeva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(14 citation statements)
references
References 58 publications
0
14
0
Order By: Relevance
“…As a dimension of preparation, clinical teams may help dismantle this false dichotomy by critically employing nuanced communication techniques and avoiding ambiguous statements in order to build shared understanding with families, even in the context of uncertainty. 42,43 Most parents rated communication and trust highly, but neither were quantitatively associated with decisional regret. Our qualitative data expand on previous findings that positive relationships and quality communication with the oncology team were associated with less decisional regret following treatment decision-making and bereavement.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As a dimension of preparation, clinical teams may help dismantle this false dichotomy by critically employing nuanced communication techniques and avoiding ambiguous statements in order to build shared understanding with families, even in the context of uncertainty. 42,43 Most parents rated communication and trust highly, but neither were quantitatively associated with decisional regret. Our qualitative data expand on previous findings that positive relationships and quality communication with the oncology team were associated with less decisional regret following treatment decision-making and bereavement.…”
Section: Discussionmentioning
confidence: 99%
“…In our in‐depth qualitative analysis of parental responses, 9 quotes from parents in our sample who felt unprepared often alluded to a false binary: giving up on their child versus trying every available intervention. As a dimension of preparation, clinical teams may help dismantle this false dichotomy by critically employing nuanced communication techniques and avoiding ambiguous statements in order to build shared understanding with families, even in the context of uncertainty 42,43 …”
Section: Discussionmentioning
confidence: 99%
“…Although most pediatric cancer patients and their parents express a desire for honest prognostic information, 18,19 deficits in both quality and quantity of prognostic communication persist 15,19,20 . Previous work revealed how oncologists infrequently discussed prognosis during disease reevaluation time points with children with advanced cancer and their families 15,21,22 . In the absence of clear prognostic communication, parents often overestimate their child’s likelihood of cure 11,15,23 and risk pursuing unrealistic primary treatment goals that increase symptoms and distress, 4 impact location of death, 10,24 and complicate grief and bereavement 25 .…”
Section: Discussionmentioning
confidence: 99%
“…15,19,20 Previous work revealed how oncologists infrequently discussed prognosis during disease reevaluation time points with children with advanced cancer and their families. 15,21,22 In the absence of clear prognostic communication, parents often overestimate their child's likelihood of cure 11,15,23 and risk pursuing unrealistic primary treatment goals that increase symptoms and distress, 4 impact location of death, 10,24 and complicate grief and bereavement. 25 This study has several limitations.…”
Section: Discussionmentioning
confidence: 99%
“…Prognostic communication remains particularly challenging when patients have cancers with poor prognoses or especially when the prognosis is less certain. In these cases, studies have shown that pediatric oncologists temper their assessment of poor prognosis when speaking with families or avoid the discussion altogether, especially during periods of disease stability or when disease progression is unclear or equivocal [ 55 , 56 , 57 ]. Whether there are similar or different types of gaps in communication about the implications of genomic testing and results in children and neonates still needs to be explored, particularly in cases of clinical uncertainty or genetic results with uncertain significance.…”
Section: Lessons In Prognostic Communication From Pediatric Oncologymentioning
confidence: 99%